1978
DOI: 10.1136/bmj.1.6127.1575
|View full text |Cite
|
Sign up to set email alerts
|

Relations between bleeding pattern, endometrial histology, and oestrogen treatment in menopausal women

Abstract: Summary and conclusionsVacuum curettage was performed on 348 women who had received various regimens of oestrogen treatment for an average of 9 7 months for climacteric symptoms. In 62 cases (18%) the specimens were unsatisfactory for histological assessment; among the remainder, however, they showed a normal endometrium in 257 cases (90%), cystic hyperplasia in 21 (7%), adenomatous hyperplasia in 7 (2%), and endometrial adenocarcinoma in one.Cyclical unopposed oral oestrogen treatment (98 cases) was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(46 citation statements)
references
References 3 publications
0
46
0
Order By: Relevance
“…The incidence of hyperplasia in women on unopposed oestrogen therapy has been estimated to be between 20% and 57% after one year depending on the dose and duration of the oestrogen. 18 -21 Adding a sequential progestogen decreases this risk, 5,22 although there may be a residual additional risk of endometrial hyperplasia despite standard regimes of progestogen. 6 For this reason continuous combined HRT has been suggested to be most favourable for the maintenance of endometrial safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of hyperplasia in women on unopposed oestrogen therapy has been estimated to be between 20% and 57% after one year depending on the dose and duration of the oestrogen. 18 -21 Adding a sequential progestogen decreases this risk, 5,22 although there may be a residual additional risk of endometrial hyperplasia despite standard regimes of progestogen. 6 For this reason continuous combined HRT has been suggested to be most favourable for the maintenance of endometrial safety.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the 1970s, clinical studies began to universally establish this link, 2,3 and since then it has been widespread practice to add in a progestogen of varying duration to counteract the malignant potential of oestrogen on the endometrium. It has been shown that adding a synthetic progestogen may effectively reduce the risk of endometrial disease 4,5 ; however, this therapy is not without its own problems. Firstly, sequential additions of progestogens often initiates a withdrawal bleed which limits its initiation and compliance for some women.…”
Section: Introductionmentioning
confidence: 99%
“…Irregular bleeding in postmenopausal women using hormonal treatment is not acceptable to users, requires endometrial investigation and as such is considered costly. The early writings on the use of progestogens documented the induction of regular withdrawal bleeding with short courses of progestogens [105]. In further attempts to eliminate the possibility of endometrial hyperplasia, the duration of progestogen usage was extended to 12 days [106].…”
Section: Evolution Of Hormonal Supplementation In the Treatment Of Pomentioning
confidence: 99%
“…Unopposed estrogen therapy, however, increases the incidence of endometrial hyperplasia [3][4][5][6] and the risk of endometrial carcinoma [7]. Addition of a progestin to estrogen replacement therapy has been shown to reduce this risk to the endometrium [8,9].…”
Section: Introductionmentioning
confidence: 99%